Free-standing ternary PtPdRu nanocatalysts with enhanced activity and durability for methanol electrooxidation. (20th December 2016) - Yang, Yi; Luo, Lai-Ming; Zhang, Rong-Hua; Du, Juan-Juan; Shen, Peng-Cheng; Dai, Zhong-Xu; Sun, Chenghua; Zhou, Xin-Wen
Graphical abstract: Dimensional free-standing PtPdRu nanocatalysts have been prepared by facile one-pot co-reduction strategy using triblock pluronic copolymer P123 as reducer, stabilizer and structure director. Dendritic PtPdRu-3D with open-framework surface and unique porous structure exhibit outstanding electrocatalytic performance for MOR. Abstract: Morphology and dimensionality are key factors to affect the catalytic activity and durability of Pt-based nanocatalysts. In this work, dendritic porous three-dimensional PtPdRu (PtPdRu-3D) nanocatalysts were fabricated by a facile one-pot hydrothermal strategy with triblock pluronic copolymer P123 as the reducer, stabilizer and structure director. Compared with zero-dimensional PtPdRu (PtPdRu-0D) and two-dimensional PtPdRu (PtPdRu-2D) and commercial Pt/C, PtPdRu-3D showed ultrahigh electrochemical surface areas (ECSA), and demonstrated an outstanding electrocatalytic activity towards methanol oxidation reaction (MOR), specifically 2.9 times higher than that of PtPdRu-0D, 1.3 times higher than PtPdRu-2D, and 1.7 times higher than commercial Pt/C. Besides, durability tests demonstrated that PtPdRu-3D displayed the lowest ECSA decay (from 100% to 80.81%) due to its 3D open-framework surface which can restrain the individual particles from aggregating.